“An assessment of strategy implementation in Zimbabwe’s Public Sector”: an empirical study of the Ministry of Health and Child Care 2009-2015. - Murove, Brian T. (Midlands State University, 2017)
The practice of strategy implementation has been important especially to public sector organizations in Zimbabwe as they complement government national policies and for key survival for government Ministries. Though a lot has been written about strategy implementation focusing on other organizations locally, regional, and international quite a few has been looked at about strategy implementation in Zimbabwe public sector. In this case this has made the researcher to research about strategy implementation using the National Health Strategy 2009-2013 of the Ministry of Health and Child Care looking on the challenges faced in strategy implementation as the main aim of the study. Literature on strategy and strategy implementation was analysed critically and gaps were also found in reviewing what other scholars brought forward concerning the study. The research methodology was a case study looking at the Ministry of Health where the researcher did his work related learning in 2015 were the researcher revealed that the Ministry have crafted over hundred strategies but not all of them were successfully implemented. The case study gave an in-depth assessment of answering the “why” questions associated with the phenomena, in this sense the research was both explanative and explorative. The research highlighted the following notable results from which conclusions were drawn; that strategy implementation fails due to lack of resources human and financial, lack of motivation and reward systems, lack of communication, there is need for training and leadership challenges and also change in government policies proved to affect strategy implementation. The results demonstrate that leadership is by far the most important factor influencing successful implementation strategy in the service sector.